2017
DOI: 10.1007/s12020-017-1432-0
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/Akt/mTOR pathway involvement in regulating growth hormone secretion in a rat pituitary adenoma cell line

Abstract: Our data confirm that mTOR inhibitors may be useful to reduce pituitary adenoma cell viability, while Erk 1/2 pathway may be considered as a useful therapeutic target to control GH secretion. Our results open the field for further studies searching for effective drugs to control GH hyper-secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Both pathways are involved in the regulation of cyclin D1 and c-MYC expression. The inhibition of PI3K/AKT/mTOR seems to be a promising therapeutic tool for aggressive somatotroph tumors [41,42] while ERK1/2 may be a useful therapeutic target to control GH secretion [43].…”
Section: Discussionmentioning
confidence: 99%
“…Both pathways are involved in the regulation of cyclin D1 and c-MYC expression. The inhibition of PI3K/AKT/mTOR seems to be a promising therapeutic tool for aggressive somatotroph tumors [41,42] while ERK1/2 may be a useful therapeutic target to control GH secretion [43].…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT signaling pathway has been associated with the occurrence of PitNET. 10,11 PTEN, a tumor suppressor gene, has been reported to negatively regulate the PI3K-AKT signaling pathway to suppress tumor progression. 12 The PTEN-PI3K/AKT signaling pathway plays important roles in mediating cancer cell migration or invasion.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Hippo pathway play roles on pituitary development and regulation of pituitary uncommitted stem/progenitor cells [55]. A previous study documented that the mTOR singling pathway effected the secretion of growth hormones by interacting with the PI3K and Akt pathways [56]. In addition, it has been suggested that overexpression of FoxO1 in pituitary decreased the expression of FSHβ [57].…”
Section: Discussionmentioning
confidence: 98%